Impact of Government Expenditure in Economic Growth of Nepal: ARDL Approach - Kunwar, Keshar Bahadur (Contemporary Research: An Interdisciplinary Academic Journal, 2019)
Public expenditure refers to the expenditure made by public authority, i.e., central government and other local bodies to carter the demand of the people. It is for protecting the citizens and for promoting their economic and social welfare. Public expenditure is one of the instruments through which government influence economic events. The specific objective of this paper is to analyze the long run and short run relationship between public expenditure and economic growth in Nepal and to examine the Causal relationship between the public expenditure and economic growth in Nepal. The study employed quantitative techniques and econometrics methods to analyze the data. This study used time series data. Data analysis begins with the testing of the unit root of the series to confirm whether the data are stationary or not. Augmented Dicky Fuller unit root test, co-integration test is employed to check the relationship of the variables under study. One period lagged LNGE has significant and positive impact on RGDP. If 1 percent increase in GE leads to increase by 34.99 percent in RGDP at 5 percent level of significance. The coefficient of error correction term (-0.782018) is significant at one percent level. Highly significant negative sign of the error correction term strengthens the presence of long-run relationship among the variables. However, the speed of adjustment from previous year’s disequilibrium in RGDP added to current year’s equilibrium is only 78.20 percent. The P-value of Breusch-Godfrey serial Correlation LM Test, Heteroscedasticity test: Breusch-Pagan-Godfrey and normality test is greater than 5 percent which is desirable. So, this model is free from auto correlation and heteroscedasticity. The residual is normally distributed.